Spinal tuberculosis: diagnosis and treatment - Laos Plasier, Eduardo Jonathan (2022)
Spinal tuberculosis accounts for 50 % of all cases of osteoarticular tuberculosis, causing disability (due to neurological complications) and deformity if left untreated. This disease is suspected based on the patient’s medical history, clinical manifestations and radiological findings. It is diagnosed by positive cultures for Mycobacterium tuberculosis, the histopathological characteristics of the condition and/or acid-fast bacilli (AFB)-positive smear tests. The main differential diagnosis of spinal tuberculosis is pyogenic spondylodiscitis. Magnetic resonance imaging is the appropriate imaging test to assess the neurological involvement and study the differential diagnosis of the disease. The main treatment is antituberculous chemotherapy, but surgery can be adjunctive in cases of complicated spinal tuberculosis. The decision of which treatment to implement depends on the neurological deficit and the resulting deformity. Laminectomy alone is contraindicated and arthrodesis implants can be used during the active infection. Despite treatment, 8 % of the patients with neurological deficit do not recover.